VALIDITAS E-MODUL BERBANTUAN SIGIL SOFTWARE PADA MATERI PERSAMAAN DAN FUNGSI KUADRAT - Sri Widha Yanti; Zulfitri Aima; Radhya Yusri (Jurnal Karya Pendidikan Matematika, 2024)
The purpose of this study was to produce a valid Sigil Software-assisted e-Module on the subject of Quadratic Equations and Functions at XI Hospitality 1 SMK Negeri 6 Padang. The method used is Research and Development (R&D) based on the Plomp model. The stages used in the plomp model are only stages 1 to stage 2, namely the initial investigation and prototyping phase concurrently testing the validity. The instruments used were validation questionnaires and interview guidelines. Based on the validator's assessment, the results of the validity of the sigil software-assisted e-Module were 90.34% in a very valid category. Based on the results of the study it was concluded that the sigil software-assisted e-Module on the material Equations and Quadratic Functions in class XI Hospitality 1 SMK Negeri 6 Padang was declared valid to be used and tested by teachers and students.